Implementasi Kurikulum Merdeka: Kecerdasan Emosional, Konsep Diri dan Pola Belajar - Saputra, Farhan (Dinasti Research, 2023)
Abstract: Implementation of the Independent Curriculum: Emotional Intelligence, Self-Concept and Learning Patterns is a scientific article of literature study within the scope of Education Management science. This article aims to build a hypothesis of the influence between variables that it will use in further research. In addition to seeing the effect of having an independent curriculum on emotional intelligence, self-concept and learning patterns. Research objects in online libraries, Google Scholar, Mendeley and other academic online media. Sourced from previous research that is relevant to this research. A descriptive qualitative method, library research, from e-books and open access e-journals. The results of this article are 1) Emotional Intelligence is related to the Implementation of the Independent Curriculum; 2) Self-Concept relates to the Implementation of the Independent Curriculum; 3) Learning Patterns are related to the Implementation of the Independent Curriculum. Abstrak: Implementasi Kurikulum Merdeka: Kecerdasan Emosional, Konsep Diri dan Pola Belajar adalah artikel ilmiah studi pustaka dalam ruang lingkup ilmu Manajemen Pendidikan. Tujuan artikel ini membangun hipotesis pengaruh antar variabel yang akan digunakan pada riset selanjutnya. Selain itu untuk melihat pengaruh dari adanya kurikulum merdeka terhadap kecerdasan emosional, konsep diri dan pola belajar. Objek riset pada pustaka online, Google Scholar, Mendeley dan media online akademik lainnya. Bersumber dari penelitian terdahulu yang relevan dengan penelitian ini. Metode kualitatif deskriptif, library research, dari e-book dan open access e-journal. Hasil artikel ini yaitu: 1) Kecerdasaran Emosional berhubungan terhadap Implementasi Kurikulum Merdeka; 2) Konsep Diri berhubungan terhadap Implementasi Kurikulum Merdeka; 3) Pola Belajar berhubungan terhadap Implementasi Kurikulum Merdeka.